Solid–gaseous phase transformation of elemental contaminants during the gasification of biomass - Jiang, Ying; Ameh, Abiba; Lei, Mei; Duan, Lunbo; Longhurst, Philip J. (Elsevier, 2015)
Disposal of plant biomass removed from heavy metal contaminated land via gasification achieves significant volume reduction and can recover energy. However, these biomass often contain high concentrations of heavy metals leading to hot-corrosion of gasification facilities and toxic gaseous emissions. Therefore, it is of significant interest to gain a further understanding of the solid–gas phase transition of metal(loid)s during gasification. Detailed elemental analyses (C, H, O, N and key metal/metalloid elements) were performed on five plant species collected from a contaminated site. Using multi-phase equilibria modelling software (MTDATA), the analytical data allows modelling of the solid/gas transformation of metal(loid)s during gasification. Thermodynamic modelling based on chemical equilibrium calculations was carried out in this study to predict the fate of metal(loid) elements during typical gasification conditions and to show how these are influenced by metal(loid) composition in the biomass and operational conditions. As, Cd, Zn and Pb tend to transform to their gaseous forms at relatively low temperatures (< 1000 °C). Ni, Cu, Mn and Co converts to gaseous forms within the typical gasification temperature range of 1000–1200 °C. Whereas Cr, Al, Fe and Mg remain in solid phase at higher temperatures (> 1200 °C). Simulation of pressurised gasification conditions shows that higher pressures increase the temperature at which solid-to-gaseous phase transformations takes place.
Keywords: Land contamination; Heavy metal; Biomass waste; Gasification; MTDATA